MODEL PRAKTIK E-BILLING SYSTEM DALAM MENDORONG KEPUASAN TAXPAYERS DAN TAX COMPLIANCE WPOP DI SURAKARTA - Fadjar Harimurti; Sriyanto Sriyanto (STIE Atma Bhakti, 2022)
Research aims to explore the causality of the relationship between system quality, information quality, and taxpayer satisfaction with tax compliance, and to examine the role of taxpayer satisfaction as a mediating variable on the effect of system quality and information quality on tax compliance. This study used a sample of 200 (Wajib Pajak Orang Pribadi) WPOP lecturers and employees at private universities in Surakarta. Sampling technique using purposive sampling. The criteria set are (1) Individual Taxpayer (WPOP) lecturers and employees at private universities (2) respondents are personal taxpayers who use E-Billing. Validity testing using Factor Analysis technique, reliability testing using Cronbach Alpha. The analytical method to test the hypothesis using Regression Analysis and Sobel Test. Results (1) system quality and information quality influencing taxpayer satisfaction, (2) system quality and information quality not influencing tax compliance, (3) taxpayer satisfaction influencing on tax compliance, (4) system quality and Information quality influencing tax compliance through taxpayers' satisfaction.